(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The aim of this paper is to present convergence results for a countable family of strict pseudocontractive mappings in Hadamard manifolds. More precisely, we employ the shrinking projection method to approximate common hierarchical fixed points of a countable family of strict pseudocontractive mappings in the setting of Hadamard manifolds. We also present some nontrivial examples to illustrate our result.